Two-choice discrimination learning in African elephants (Loxodonta africana) - Charles Hyatt (Pachyderm)
A study of two-choice discrimination learning across 22 pattern pairs was conducted with three African elephants (Loxodonta africana) at the Atlanta/Fulton County Zoo with rates of acquisition and retention observed to be similar to those earlier reported for the Asian species (Elephas maximus). A significant difference was found in trials to criterion for the second half of the stimulus pairs compared with the first, indicating potential development of the learning set; after seven months with no exposure to the pattern problems, one of the subjects correctly selected the appropriate pattern on 16 of 20 pairs, and the other subject demonstrated improvement on a computer joystick task. This study extends learning research to the African species and indicates potential for further cognitive skill development.